The Anglo-Saxon library Michael Lapidge. - Lapidge, Michael (Oxford University Press, 2008)
Michael Lapidge provides the first comprehensive survey of the nature and holdings of libraries in Anglo-Saxon England. He gives details of the definitive catalogue of all works known in England before 1100.